Pendidikan Islam Sebagai Subsistem Pendidikan Nasional - Akip, Muhamad; Rahmat, Azwar (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2022)
This study was conducted to determine the subsystem of Islamic education in National Education, with the aim of looking at the existence and the basis of education for the implementation and recognition of Islamic education as a sub-system of national education which is assumed to be a product of dichotomy and discrimination. This type of research is a literature study with a qualitative description by analyzing and interpreting the data. Islamic education has the right to gain legitimacy to develop in meeting the educational needs of Muslims who are the majority in Indonesia and the State's appreciation of Islamic education that has been going on since the birth of Islam such as kuttab, halaqah, suffah, and madrasah, through Law No. 2 of 1989 and Law No. 20 of 2003, namely for the first time Islamic education became a national education subsystem and as a solution in responding to the challenges of the times and answering the problem of discrimination and the dichotomy between education under the auspices of the Ministry of Religion and the Ministry of Education and Culture although until now Islamic education is still feeling it, such as the refusal of ASN to PGMI Alumni at the Ministry of Education and Culture while PGSD Alumni can walk under the auspices of the Ministry of Religion.